Athletes: Fit but Unhealthy? - Maffetone, Philip B. (Sports Med Open, 2016)
While the words “fit” and “healthy” are often used synonymously in everyday language, the terms have entirely separate meanings. Fitness describes the ability to perform a given exercise task, and health explains a person’s state of well-being, where physiological systems work in harmony. Although we typically view athletes as fit and healthy, they often are not. The global term we place on unhealthy athletes is the overtraining syndrome. In this current opinion, we propose that two primary drivers may contribute to the development of the overtraining syndrome, namely high training intensity and the modern-day highly processed, high glycemic diet. Both factors elicit a sympathetic response through the hypothalamic-pituitary-adrenal axis, in turn driving systemic reactive oxygen species production, inflammation, and a metabolic substrate imbalance towards carbohydrate and away from fat oxidation, manifesting in an array of symptoms often labeled as the overtraining syndrome. Ultimately, these symptoms reveal an unhealthy athlete. We argue that practitioners, scientists, and athletes may work towards health and alleviate overtraining syndrome by lowering training intensity and removing processed and/or high glycemic foods from the diet, which together enhance fat oxidation rates. Athletes should be fit and healthy.